Pengaruh Budaya Sekolah, Kepuasan Kerja Dan Motivasi Kerja Terhadap Komitmen Kerja Guru Di Sekolah Inklusif Jenjang SD Kecamatan Babul Makmur - Vivin Melina Matondang; Sari Rizki; Indra Utama (Journal on Education, 2024)
The aims of this research are (1) To analyze the positive and significant direct influence of school culture on the work commitment of elementary school teachers in Babul Makmur District, (2) To analyze achievement motivation moderating the influence of school culture on the work commitment of elementary school teachers in Babul Makmur District. , (3) To analyze achievement motivation moderating the influence of school culture on the work commitment of elementary school teachers in Babul Makmur sub-district. This research uses a quantitative approach with an associative method, a population and sample of 53 inclusive school teachers using a probability sampling method, data collection techniques using a Likert scale questionnaire. The school culture variable has a tcount value of 4,612, where this value is greater than the ttable value. The ttable value is obtained by ttable = t (a/2; n - k -1) = t (0.05/2;51) = 2.008 with unstandardized beta coefficients of 0.385 and a significance level of 0.000 which is smaller than 0.05, so the first hypothesis is accepted. The moderating variable School Culture*Job Satisfaction has a t-value of -0.911. The value obtained is smaller than ttable. The ttable value = t(a/2; n - k -1) = t (0.025;51) = 2.008 with an unstandardized beta coefficient value of -0.021 and a significance level of 0.367 which is greater than 0.05, so the second hypothesis is rejected. This shows that job satisfaction does not moderate the influence of school culture on teacher work commitment. The moderating variable School Culture*Work Motivation has a t-value of 0.992. The value obtained is smaller than ttable. The ttable value = t(a/2; n - k -1) = t (0.025;51) = 2.008 with an unstandardized beta coefficient value of 0.022 and a significance level of 0.236 which is greater than 0.05, so the third hypothesis is also rejected. This shows that work motivation does not moderate the influence of school culture on teacher work commitment.